Técnica didáctica "ASERTUS" para incentivar el aprendizaje de la asertividad en los estudiantes del tercer grado, nivel primario en el Área Personal Social, en la Institución Educativa Nº 00536 Manuel Segundo del Águila Velásquez - Vílchez Gonzales, Silsley (2008)
The present investigation has had as general objective, to demonstrate that the application of the Didactic Technique "ASERTUS" influences significantly in the learning of the assertiveness in the students of the third grade, in the área of Personal Social, of the lnstitution Educational Nº 00536 Manuel Second of the Eagle Velásquez, in the year 2007. Whose the fundamental purpose is to make the student to develop his social abilities, his reflexive thought, his creative capacities that allow him to be unwrapped appropriately at every moment and circumstance of his life. The study, has as theoretical sustenances: the physiologic theory According to Maslow, the theory of the multiple intelligence According to Gardner, the theory of the significant learning According to Ausubel, the theory psicosocial of Vygotsky, the theory of the social abilities According to Nuns and the theory of the learning for observation According to Bandura. Supported in these theoretical • positions, the hypotheses were formulated: Alternativa hypothesis: lf the Didactic Technique "ASERTUS" is applied then it will influence significantly in the learning of the assertiveness in the students of the third grade, in .the área of Personal Social, of the lnstitution Educational Nº 00536 Manuel Second of the Eagle Velasquez. Null hypothesis: lf the Didactic Technique "ASERTUS" is applied then it won't influence significantly in the learning of the assertiveness in the students of the third grade, in the Area of Personal Social, of the lnstitution Educational Nº 00536 Manuel Second of the Eagle Velásquez. The study sample was conformed by 30 students, 13 males and 17 women, to which was denominated experimental group. Also, for the utilized design it was considered a group denominated control that was conformed by 25 students 12 males and 13 women. So much to the experimental group as to the group control, he/she was applied a pre test to determine the previous assertiveness level to the stimulus. Then five learning sessions were developed in those that he/she put into practice the didactic technique "ASERTUS" like stimulus for the learning of the assertiveness in the students of the experimental group. Finally the search test l was applied to determine the goods of the didactic technique "ASERTUS." After the analysis and respective interpretation of the results, it was demonstrated that the application of the didactic technique "ASERTUS" influences significantly in the learning of the assertiveness in the students of the third grade of the lnstitution Educational N° 00536 Manuel Second of the Eagle Velásquez, Rioja.